2014
DOI: 10.1371/journal.pone.0091008
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Neural Systems Represent Cognitive Effort and Reward Anticipation

Abstract: Anticipating a potential benefit and how difficult it will be to obtain it are valuable skills in a constantly changing environment. In the human brain, the anticipation of reward is encoded by the Anterior Cingulate Cortex (ACC) and Striatum. Naturally, potential rewards have an incentive quality, resulting in a motivational effect improving performance. Recently it has been proposed that an upcoming task requiring effort induces a similar anticipation mechanism as reward, relying on the same cortico-limbic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
201
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(219 citation statements)
references
References 84 publications
15
201
3
Order By: Relevance
“…Here we show engagement of these basal forebrain structures (VS and extended amygdala), but importantly in the absence of explicit reward, prior knowledge of effort-action outcome contingencies, and choice (key aspects of effort-based discounting/decision-making tasks). Nonetheless, the present findings converge with previous suggestions that VS recruitment in difficult tasks reflects stimuli saliency (Schouppe et al, 2014;Zink et al, 2006), and mediates response vigour (Vassena et al, 2014). In line with endogenous activation of midbrain structures when task demands are high (Boehler et al, 2011), our findings provide novel evidence for a more general role of these areas in intrinsic motivational processes that translate goal pursuit into effort exertion and motor output.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Here we show engagement of these basal forebrain structures (VS and extended amygdala), but importantly in the absence of explicit reward, prior knowledge of effort-action outcome contingencies, and choice (key aspects of effort-based discounting/decision-making tasks). Nonetheless, the present findings converge with previous suggestions that VS recruitment in difficult tasks reflects stimuli saliency (Schouppe et al, 2014;Zink et al, 2006), and mediates response vigour (Vassena et al, 2014). In line with endogenous activation of midbrain structures when task demands are high (Boehler et al, 2011), our findings provide novel evidence for a more general role of these areas in intrinsic motivational processes that translate goal pursuit into effort exertion and motor output.…”
Section: Discussionsupporting
confidence: 91%
“…The VS (and globus pallidus) is well documented to be involved in motivating effort exertion in rewarding contexts (Adam et al, 2013;Le Bouc and Pessiglione, 2013;Pessiglione et al, 2007;Schmidt et al, 2009;Schmidt et al, 2012), and effort-related decision-making in both humans and animals (Salamone and Correa, 2012). Activity of VS has shown to reflect exertion costs and costbenefit valuations (Croxson et al, 2009;Kurniawan et al, 2010;Prévost et al, 2010), as well as anticipation of reward and high effort (Vassena et al, 2014). Here we show engagement of these basal forebrain structures (VS and extended amygdala), but importantly in the absence of explicit reward, prior knowledge of effort-action outcome contingencies, and choice (key aspects of effort-based discounting/decision-making tasks).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, with stronger control there are less errors, faster RTs, and smaller congruency effects. This occurs both proactively (e.g., because the reward at stake is higher or because the upcoming task is difficult; Janssens, De Loof, Pourtois, & Verguts, 2016;Vassena et al, 2014;Padmala & Pessoa, 2011) and reactively (e.g., in response to current trial processing difficulty or after an error or incongruent trial; Gratton, Coles, & Donchin, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Inactivation of this neurocircuitry results in decreases in effort-related motivated behavior (Salamone et al, 2007). Human imaging studies have also identified the dorsal anterior cingulate cortex (dACC; Croxson et al, 2009;Prevost et al, 2010;Vassena et al, 2014) and the ventral striatum (VS; Croxson et al, 2009;Kurniawan et al, 2013;Schouppe et al, 2014;Vassena et al, 2014) as the neural correlates of effort-based motivation.…”
Section: Introductionmentioning
confidence: 99%